2018
DOI: 10.1002/slct.201802565
|View full text |Cite
|
Sign up to set email alerts
|

Anchimerically Assisted Cleavage of Aryl Methyl Ethers by Aluminum Chloride‐Sodium Iodide in Acetonitrile

Abstract: A practical method is developed for the cleavage of catechol monomethyl ethers and o-carbonylphenyl methyl ethers using aluminum chloride and sodium iodide in acetonitrile. Acid scavengers such as 1,3-diisopropylcarbodiimide and CaO are used to prevent acid-labile functional groups from sidereactions. This method is efficient for the deprotection of various o-hydroxyphenyl methyl ethers such as acetovanillone, eugenol, guaiacol, vanillin, isovanillin and ortho-vanillin. The AlCl 3 -NaI system is less efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Following a very recent report describing clean demethylation of various ortho-methoxyphenols to catechol by treatment with a combination of AlCl 3 and NaI in acetonitrile using N,N′diisopropylcarbodiimide (DIC) as the acid scavenger, the reaction failed and 11 was recovered almost quantitatively. 20 However, inspired by this work and our previous results, we decided to treat 11 with BBr 3 (5 equiv) in DCM in the presence of DIC (2 equiv) to prevent side reactions probably due to byproducts of the reaction such as methyl bromide, hydrobromic acid, and boronic acid. Pleasingly, (+)-and (−)-fumimycin methyl ester 16 were obtained cleanly and in very good yield.…”
mentioning
confidence: 99%
“…Following a very recent report describing clean demethylation of various ortho-methoxyphenols to catechol by treatment with a combination of AlCl 3 and NaI in acetonitrile using N,N′diisopropylcarbodiimide (DIC) as the acid scavenger, the reaction failed and 11 was recovered almost quantitatively. 20 However, inspired by this work and our previous results, we decided to treat 11 with BBr 3 (5 equiv) in DCM in the presence of DIC (2 equiv) to prevent side reactions probably due to byproducts of the reaction such as methyl bromide, hydrobromic acid, and boronic acid. Pleasingly, (+)-and (−)-fumimycin methyl ester 16 were obtained cleanly and in very good yield.…”
mentioning
confidence: 99%
“…Exhaustive demethylation was achieved for the deprotection of catechol dimethyl ether ( 3j′) and 1,4‐dimethoxybenzene ( 3c′ ) that afforded catechol ( 4 j ) and quinol ( 4 c ) in 93% and 57% yields, respectively. The higher ether cleaving efficiencies for catechol monomethyl ether ( 3 j ) and catechol dimethyl ether ( 3j′ ) compared to that of 1,4‐dimethoxybenzene ( 3c′ ) might be attributed to assistance of the neighboring group participation effect . It is noteworthy that essentially quantitative yields were obtained for the demethylation of guaiacol ( 3 j ) and 1,2‐dimethoxybenzene ( 3 j ), and the yield for the later was comparable to that by aluminum triiodide .…”
Section: Resultsmentioning
confidence: 87%
“…2,5‐Dimethoxybenzaldehyde ( 3 u ) was demethylated to give 5‐hydroxysalicylaldehyde ( 4 u ) as the major product (61%) along with trace amount of 5‐methoxysalicylaldehyde ( 4u′ ). We have noted that when 3 u was treated by AlCl 3 ‐NaI under the same conditions, the major product was 5‐methoxysalicylaldehyde ( 4u′ ) . These results indicated that the aluminum‐iodine reagent system is a more powerful ether cleaving agent than AlCl 3 ‐NaI.…”
Section: Resultsmentioning
confidence: 99%
“…143 A quantitative yield (99%) can be reached using aluminum iodide with an excess of pyridine in acetonitrile 144 or aluminum chloride with 1,3diisopropylcarbodiimide (DIC) and an excess of sodium iodide. 145 Scheme 12. Oxidative O-demethylation of eugenol.…”
Section: O-demethylationmentioning
confidence: 99%